Identification of the C-terminal activation domain of the NeuroD-related factor (NDRF) - Konishi, Yoshiyuki (Oxford University Press, 2000)
NeuroD-related factor (NDRF) is a basic helix–loop–helix (bHLH) protein whose expression is restricted to the central nervous system, and is considered to be responsible for maintenance of differentiated neurons as well as neurogenesis. NDRF structurally resembles NeuroD in the bHLH region and can induce neurogenesis ectopically in ectodermal cells of the Xenopus embryo. In this study, we delineated the functional domains of NDRF. Using GAL4/NDRF fusion proteins, we identified the C-terminal activation domain (C-AD) in NDRF between amino acid positions 294 and 383. This region was highly homologous to one part of the activation domain of NeuroD. We further investigated the transactivational function of C-AD in the mouse type 1 inositol 1,4,5-trisphosphate receptor promoter, which has an NDRF site. Truncation of C-AD resulted in reduction of the activation function, whereas the DNA-binding specificity was not affected. These results suggest that C-AD has a stimulatory function in the mammalian nervous system.